Implication of Tidal Forcing Effects on the Zonal Variation of Solstice Equatorial Plasma Bubbles. Issue 3 (1st March 2021) - Chang, Loren C.; Salinas, Cornelius Csar Jude H.; Chiu, Yi‐Chung; Jones, McArthur; Rajesh, P. K.; Chao, Chi‐Kuang; Liu, Jann‐Yenq; Lin, Charles C. H.; Hsiao, Tung‐Yuan
Abstract: Equatorial plasma bubbles (EPBs) are plasma depletions that can occur in the nighttime ionospheric F region, causing scintillation in satellite navigation and communications signals. Past research has shown that EPB occurrence rates are higher during the equinoxes in most longitude zones. An exception is over the central Pacific and African sectors, where EPB activity has been found to maximize during solstice. Tsunoda et al. (2015) hypothesized that the solstice maxima in these two sectors could be driven by a zonal wavenumber 2 atmospheric tide in the lower thermosphere. In this study, we utilize satellite observations to examine evidence of such a wave‐2 feature preconditioning the nighttime ionosphere to favor higher EPB growth rates over these two regions. We find the postsunset total electron content (TEC) observed by FORMOSAT‐3/COSMIC (Constellation Observing System for Meteorology, Ionosphere, and Climate) during boreal summer from 2007 to 2012 exhibits a wave‐2 zonal distribution, consistent with elevated vertical plasma gradients favorable for EPB formation. Numerical experiments are also carried out to determine whether such an ionospheric wave‐2 can be produced as a result of vertical coupling from atmospheric tides with zonal wavenumber 2 in the local time frame. We find that forcing from these tidal components produced increases in the Rayleigh‐Taylor growth rate over both sectors during solar maximum and minimum, as well as wave‐2 modulations on vertical ion drift, ion flux convergence, and nighttime TEC. Our results are consistent with the aforementioned hypothesis over both regions with vertical coupling effects from atmospheric tides preconditioning the nighttime ionosphere to favor higher EPB growth rates. Key Points: Equatorial plasma bubble (EPB) variation over the Central Pacific and African sectors hypothesized to be caused by tidal forcing Constellation Observing System for Meteorology, Ionosphere, and Climate total electron content (COSMIC TEC) shows recurrent maxima of wave‐2 tidal signatures over both regions during nighttime, favoring higher EPB growth rates Model results show atmospheric tides can drive increases in Rayleigh‐Taylor growth rates over both regions that vary with solar cycle